2010
DOI: 10.1007/s10493-010-9375-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-feeding as a route for transmission of Rickettsia conorii israelensis between Rhipicephalus sanguineus ticks

Abstract: Rickettsia conorii is widely distributed in Europe, Asia, and Africa. The brown dog tick, Rhipicephalus sanguineus, is the recognized vector of R. conorii. In this study, we assessed the efficiency of R. conorii israelensis transmission between co-feeding Rh. sanguineus ticks. Infected Rh. sanguineus adults and uninfected nymphs were fed simultaneously upon either naïve dogs or a dog previously exposed to this agent. When ticks were placed upon naïve dogs, 92-100% of nymphs acquired the infection and 80-88% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 40 publications
2
49
1
3
Order By: Relevance
“…24, 25, 28, 29), whereas rickettsial transmission was demonstrated by fever and seroconversion in 2 guinea pigs (nos. 26, 27). PCR on ticks demonstrated no rickettsial DNA in adult ticks that molted from engorged nymphs recovered from guinea pigs 18–25 and 28–29, which did not develop fever or serocont.…”
Section: Resultsmentioning
confidence: 99%
“…24, 25, 28, 29), whereas rickettsial transmission was demonstrated by fever and seroconversion in 2 guinea pigs (nos. 26, 27). PCR on ticks demonstrated no rickettsial DNA in adult ticks that molted from engorged nymphs recovered from guinea pigs 18–25 and 28–29, which did not develop fever or serocont.…”
Section: Resultsmentioning
confidence: 99%
“…While A. americanum has experimentally transmitted R. parkeri transstadially and transovarially (Goddard 2003), the presence of R. parkeri in D. variabilis observed in this study might have been due to incidental infection during cofeeding since D. variabilis and A. maculatum were coexistent at the landfill collection site and are likely to have shared hosts. Pathogen transmission via tick cofeeding has been observed for a wide range of viruses (Randolph et al 1996), but has also been demonstrated for bacteria, including Borrelia burgdorferi Rais 1996, Patrican 1997) and, more recently, R. conorii (Zemtsova 2010). In addition to R. parkeri, the SFG screen of A. maculatum detected the novel SFG Rickettsia species tentatively designated ''Candidatus Rickettsia andeanae'' (Blair et al 2004, Jiang et al 2005, Paddock et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…However, dogs with different genetic backgrounds appear to differ in their susceptibility to Rickettsia conorii subsp. israelensis infection (38). Recent studies of experimental infections of capybaras (Hydrochoerus hydrochaeris), opossums (Didelphis aurita), and domestic dogs with a highly virulent strain of R. rickettsii showed that these animals developed rickettsemia of sufficient magnitude to infect A. cajennense or Rhipicephalus sanguineus ticks during feeding (26,28,39,40).…”
Section: Figmentioning
confidence: 99%
“…R. conorii subsp. israelensis was shown to be successfully transmitted transstadially in Rhipicephalus sanguineus from nymphs to adults (38). However, the vertical transmission of this bacterium in its host ticks has not yet been demonstrated.…”
Section: Tick-borne Rickettsiae In Europe Species Identified As Pathomentioning
confidence: 99%